2020
DOI: 10.21203/rs.3.rs-38623/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Tele-ECG consulting and outcomes on primary care patients in a low-to-middle income population: The first experience from Makassar Telemedicine Program, Indonesia

Abstract: Background: Telemedicine has been a popular tool to overcome the lack access to healthcare facilities, primarily in underprevilaged populations. We aimed to describe and assess the implementation of tele-electrocardiography (ECG) program in primary care settings in Indonesia, and subsequently examine the short- and mid-term outcomes of patients those received tele-ECG consultation.Methods: A total of 505 ECG recordings from thirty primary care centers were transmitted to Makassar Cardiac Center, Indonesia from… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…Remote blood glucose monitoring linked to web-based cloud technologies allows for the transfer of continuous glucose monitoring (CGM) data directly to healthcare professionals (e.g. intermittent CGM) [73,74]. However, the suitability of these telemedicine activities for the individual should be carefully considered, as they may not be effective in all cases [71,75].…”
Section: Tzd Thiazolidinedionementioning
confidence: 99%
“…Remote blood glucose monitoring linked to web-based cloud technologies allows for the transfer of continuous glucose monitoring (CGM) data directly to healthcare professionals (e.g. intermittent CGM) [73,74]. However, the suitability of these telemedicine activities for the individual should be carefully considered, as they may not be effective in all cases [71,75].…”
Section: Tzd Thiazolidinedionementioning
confidence: 99%
“…The tele-ECG has been instrumental in reducing the un-need patients referral and has allowed better allocation of resources through early triage of patients with acute CVD, based on their symptoms and examinations. Our previous study showed that 100% of ECG recordings were transmitted successfully and qualified for analysis; and thus, we suggest that tele-ECG can be implemented in Indonesian primary care settings with limited resources [6]. In traditional manner, when tele-ECG program was not applied, the ECG solely interpreted by the GP in the primary care center; or even worse, the ECG are not available as a basis healthcare service in several primary centers.…”
Section: Tele-electrocardiography In Low-and Middle-income Countriesmentioning
confidence: 97%
“…In traditional manner, when tele-ECG program was not applied, the ECG solely interpreted by the GP in the primary care center; or even worse, the ECG are not available as a basis healthcare service in several primary centers. By implementing this tele-ECG program, the consultation to the expert cardiologists may assist the GPs for immediate triage, resulting in a higher rate of early hospitalization for indicated patients, and eventually could reduce the mortality rate of acute CVD in Indonesia [6]. The flowchart of utilization and final purpose of tele-ECG is shown in Figure 1.…”
Section: Tele-electrocardiography In Low-and Middle-income Countriesmentioning
confidence: 99%